Faktor Risiko Kejadian Atonia Uteri - Mega Lestari; Pungky Mulawardhana; Budi Utomo (Universitas Airlangga, 2019)
Introduction: Postpartum Hemorrhage is one of the main cause of maternal morbidity and mortality worlwide. Every 4 minutes one woman is estimated dead by this case. The cause of postpartum hemorrhage is known as ‘4 T’s’ (tone, tissue, trauma, and thrombin). Common aetiology of hemorrhage postpartum is uterine atony. Uterine atony can be caused by several risk factors . The aim of this study is to determine the correlation between advanced maternal age, grande multiparity, uterine overdistension, labour augmented, and prolonged labour as risk factors with the incidence of uterine atony.Methods: This study was an analysis of observational study with case-control design conducted at a tertiary hospital in Surabaya. The population was all medical record of postpartum women who had hemorrhage in 2016-2018. The case group was postpartum woman who had hemorrhage due to uterine atony and the control group due to other causes. The sample size of the case group was 37 respondents and the control group was 35 respondents, they were obtained through purposive sampling. The independent variables in this study was maternal age, parity, uterine overdistension, labour augmented, and prolonged labour; the dependent variable was uterine atony. Univariate analysis was used to describe respondent’s characteristic and bivariate analysis was used to determine the correlation between risk factors and the incidence of uterine atony. Fisher Exact was used to analyze the data with α= 0,05.Results: Fisher Exact showed there was correlation between uterine overdistension and uterine atony (p value=0,036; OR= 4,423; 95% CI 1,023-27,267) on the other hand it showed no correlation between maternal age, parity, augmented labour, and prolonged labour with uterine atony (p value >0,05).Conclusion: Increased awareness of pre-conceptual care and early detection of risk factors are needed to reduce the risk factors of the incidence of uterine atony especially in uterine overdistension.